Structure-guided engineering of a mutation-tolerant inhibitor peptide against variable SARS-CoV-2 spikes - Shun Nakamura; Yukihiro Tanimura; Risa Nomura; Hiroshi Suzuki; Kouki Nishikawa; Akiko Kamegawa; Nobutaka Numoto; Atsushi Tanaka; Shigeru Kawabata; Shoichi Sakaguchi; Akino Emi; Youichi Suzuki; et al. (Proceedings of the National Academy of Sciences, 2025)
Pathogen mutations present an inevitable and challenging problem for therapeutics and the development of mutation-tolerant anti-infective drugs to strengthen global health and combat evolving pathogens is urgently needed. While spike proteins on viral surfaces are attractive targets for preventing viral entry, they mutate frequently, making it difficult to develop effective therapeutics. Here, we used a structure-guided strategy to engineer an inhibitor peptide against the SARS-CoV-2 spike, called CeSPIACE, with mutation-tolerant and potent binding ability against all variants to enhance affinity for the invariant architecture of the receptor-binding domain (RBD). High-resolution structures of the peptide complexed with mutant RBDs revealed a mechanism of mutation-tolerant inhibition. CeSPIACE bound major mutant RBDs with picomolar affinity and inhibited infection by SARS-CoV-2 variants in VeroE6/TMPRSS2 cells (IC 50 4 pM to 13 nM) and demonstrated potent in vivo efficacy by inhalation administration in hamsters. Mutagenesis analyses to address mutation risks confirmed tolerance against existing and/or potential future mutations of the RBD. Our strategy of engineering mutation-tolerant inhibitors may be applicable to other infectious diseases.